APPROPRIATION AND ANALYSIS OF COST OF IMPLANTATION OF PEACH ORCHARD - PENTEADO JUNIOR, Joel Ferreira; MAY-DE-MIO, Louise Larissa; MONTEIRO, Lino Bittencourt; GAYER NETO, Waldomiro (Scientia Agraria, 2008)
This work was carried through in the city of Araucária, located in the region metropolitan of Curitiba, PR. The objectives were present calculations and analysis of the costs of implantation in peach orchards, and also, to construct and to offer an spreadsheet detailed with coefficients technician and values, that allow to the most different substitutions of the values and pointers, thus making possible to personalize each in case that, to be used as a tool for the management of agricultural establishments. The implantation and formation costs of 1,0 ha of the culture, contemplating until the first year of plantation, had reached R$ 8849,00 where the most significant components in the composition of the costs were, the cost of seedlings and services, representing 87.67% of the total. Individually, the number of plants for hectare has great importance in the composition of the costs for hectare and in this in case that it represented, 56.50% of the total.